2021
DOI: 10.1016/j.fsigen.2021.102475
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel sequencing of 165 ancestry-informative SNPs and forensic biogeographical ancestry inference in three southern Chinese Sinitic/Tai-Kadai populations

Abstract: Ancestry informative markers (AIMs), which are distributed throughout the human genome, harbor significant allele frequency differences among diverse ethnic groups. The use of sets of AIMs to reconstruct population history and genetic relationships is attracting interest in the forensic community, because biogeographic ancestry information for a casework sample can potentially be predicted and used to guide the investigative process. However, subpopulation ancestry inference within East Asia remains in its inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…Southwestern East Asia is one of the most ethnolinguistically diverse regions around the world. Genetic origin, subsequent migration, isolation, plausible admixture, and local adaptation history of ethnolinguistic southern Chinese populations were widely discussed via different genetic markers, mainly including autosomal short tandem repeats (STRs), single nucleotide polymorphism (SNPs), and copy number variations (CNVs) (Chen et al, 2019;Zhang C. et al, 2019;He et al, 2021;Liu et al, 2021a). However, most of these studies focused on the genetic variations and forensic features of low-density genetic markers in the Han Chinese populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Southwestern East Asia is one of the most ethnolinguistically diverse regions around the world. Genetic origin, subsequent migration, isolation, plausible admixture, and local adaptation history of ethnolinguistic southern Chinese populations were widely discussed via different genetic markers, mainly including autosomal short tandem repeats (STRs), single nucleotide polymorphism (SNPs), and copy number variations (CNVs) (Chen et al, 2019;Zhang C. et al, 2019;He et al, 2021;Liu et al, 2021a). However, most of these studies focused on the genetic variations and forensic features of low-density genetic markers in the Han Chinese populations.…”
Section: Introductionmentioning
confidence: 99%
“…There are also important studies focused on the genetic relationships between central Hans and their neighbors (e.g., Han, Manchu, Mongolian, and Tujia). However, all of these studies mainly focused on the patterns from the shared alleles and sample frequency spectrum of independent SNPs (Chen et al, 2021;He et al, 2021) and lacked evidence from a fine-scale genetic structure based on the shared haplotype chunks (successive linked SNP fragments) and uniparental haplogroup lineages.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of uniparentally inherited Y chromosome haplogroup and mitochondrial haplogroup, Chen et al made a preliminary exploration focused on the forensic parameters and genetic structure of the Tai–Kadai-speaking populations in Guizhou and the population genetic relationship based on the short tandem repeat (STR) on the autosome and X/Y-chromosomes ( Chen et al, 2018c ). Further genetic studies had focused on the population admixture history and genetic diversity of Tai–Kadai-speaking Gelao and Bouyei by insertion/deletion polymorphisms (InDels) and ancestry-informative single-nucleotide polymorphism (AISNPs) ( He et al, 2019a ; He et al, 2019b ; He et al, 2021b ). The obtained research results showed a significant genetic interaction between Tai–Kadai- and Hmong–Mien-speaking populations ( He et al, 2019a ; He et al, 2019b ; He et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Further genetic studies had focused on the population admixture history and genetic diversity of Tai–Kadai-speaking Gelao and Bouyei by insertion/deletion polymorphisms (InDels) and ancestry-informative single-nucleotide polymorphism (AISNPs) ( He et al, 2019a ; He et al, 2019b ; He et al, 2021b ). The obtained research results showed a significant genetic interaction between Tai–Kadai- and Hmong–Mien-speaking populations ( He et al, 2019a ; He et al, 2019b ; He et al, 2021b ). However, these studies were conducted based on low-density genetic markers and were mainly focused on exploring forensic characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation